Janka w (literackim) zwierzyńcu - Wysłouch, Seweryna (My University, 2013)
"Pisarze w zwierzyńcu" [Writers in an Animal Park] by Janina Abramowska are an admirable display of erudition, originality of interpretation, and careful composition. The text brings on reflections about the animal world, its distinct quality, and the animal narrative perspective, which the author has not noticed.
Janka in a (Literary) Animal Park
Keywords: animals; bestiary; anthropomorphisation; narrative perspective